Laparoscopic versus open appendectomy during pregnancy - Alkatary, Mohammed M.; Bahgat, Nagwan A. (International Surgery Journal, 2017)
Background: Various causes can be claimed for abdominal pain during pregnancy. Acute appendicitis is the most common cause of abdominal pain during pregnancy. Diagnosis of acute appendicitis during pregnancy is a quiet challenging due to anatomical and physiological changes that occur during pregnancy. Methods: On the period from January 2010 to January 2012we reviewed the number of pregnant patients presented to our facility by abdominal pain and diagnosed as acute appendicitis. Total number was 23 patients. 2 patients were excluded as their magnetic resonance imaging showed normal appendix and were discharged. 6 patients presented on the 1st trimester, 7 patients presented on the 2nd trimester and 8 patients on the 3rd trimester. Laparoscopic appendectomy performed in 9 patients while 12 patients had open appendectomy. Results: The operative time on the laparoscopic group ranged from 50-80 minutes while on the open appendectomy ranged from 40-60 minutes. The length of stay after laparoscopic procedure was 1.5-3 days in comparison to 3-5 days following open appendectomy. Postoperative wound infection detected in 2 patients after open appendectomy (16%) compared with 1 patient (11%) following laparoscopic appendectomy. The postoperative pathology was classified as normal appendix, suppurated appendix and complicated appendix. Table 2 showed the postoperative pathological examination. Preterm labor detected in one patient only had open appendectomy. Fetal outcome was evaluated by Apgar scoring together with fetal length and weight after delivery with no significant abnormality. Conclusions: Laparoscopic appendectomy is safe for both the mother and the fetus during pregnancy irrespective of gestational age, and the procedure is associated with a low risk of post-operative complications.